PELATIHAN PEMANFAATAN WORDWALL DAN GOOGLE EARTH SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DI SD NEGERI WARU 01 - Luqman Rohmad Maghribi; Dede Rizki Saepullah; Anisa Khayati Nur Kafah; Pipit Novita; Marshandra Sumantri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This community service program aimed to improve the digital competence of elementary school teachers at SD Negeri Waru 01, Parung, Bogor Regency, through training on the utilization of Wordwall and Google Earth as interactive learning media. The background of this study is the gap between the demands of 21st century education and the reality of conventional learning practices still prevalent in elementary schools. The program was implemented over six months through workshops, direct practice (micro-teaching), and intensive mentoring. Results showed significant improvement in teachers' digital literacy, enabling them to independently design interactive learning activities using Wordwall (gamification quizzes, random wheels) and navigate Google Earth features for contextual IPAS learning. Students demonstrated increased motivation, active participation, and improved spatial-visual literacy. The integration of interactive digital media aligns with findings that game-based learning and socio-educational environments are key predictors of eco-digital literacy development. The program also produced a sustainable digital learning repository aligned with the school curriculum, supporting the implementation of the Merdeka Curriculum in elementary education.